Improving executive sponsorship of projects : a holistic approach - Chandler, Dawne E. (Portfolio and project management collection., 2017)
This book is a resource for senior managers looking to enhance project outcomes by improving executive project sponsorship. It is also a source for project managers and sponsoring executives seeking information to improve sponsor effectiveness. Improving Executive Sponsorship of Projects addresses gaps in current project management literature. From a senior management perspective, the gap is the lack of resources explaining why and how to establish a program to improve executive sponsorship strategically across an organization. From a tactical perspective, the gap is a scarcity of actionable materials to clarify roles, responsibilities, expected behaviors, and identify support necessary for improving sponsor effectiveness. The authors identify key factors to consider before creating an executive sponsorship improvement program or enhancing an existing one and explain why executive sponsorship is important to an organization, how an organization's culture influences the effectiveness of the sponsor role, and why project management standards are critical to success. They explore what roles, responsibilities, and behavior should be considered and how to determine whether the person in the sponsor role is the right person and prepared to do the job. Finally, the book provides a process, with tools, to assess an organization's readiness to implement an executive sponsorship program, develop a plan for improvement, and monitor the progress of a program once it has begun.